Mister Exam
Lang:
EN
EN
ES
RU
Other calculators:
Integral Step by Step
Derivative Step by Step
Differential equations Step by Step
How to use it?
Limit of the function
:
Limit of pi-2*acot(x)/(-1+e^(3/x))
Limit of tan(8*x)/sin(5*x)
Limit of n/factorial(n)
Limit of cosh(n)/cosh(1+n)
Graphing y =
:
e^x*cos(x)
Integral of d{x}
:
e^x*cos(x)
Derivative of
:
e^x*cos(x)
Identical expressions
e^x*cos(x)
e to the power of x multiply by co sinus of e of (x)
ex*cos(x)
ex*cosx
e^xcos(x)
excos(x)
excosx
e^xcosx
Similar expressions
e^x*cosx
Limit of the function
/
e^x*cos(x)
Limit of the function e^x*cos(x)
at
→
Calculate the limit!
v
For end points:
---------
From the left (x0-)
From the right (x0+)
The graph:
from
to
Piecewise:
{
enter the piecewise function here
The solution
You have entered
[src]
/ x \ lim \E *cos(x)/ x->-oo
lim
x
→
−
∞
(
e
x
cos
(
x
)
)
\lim_{x \to -\infty}\left(e^{x} \cos{\left(x \right)}\right)
x
→
−
∞
lim
(
e
x
cos
(
x
)
)
Limit(E^x*cos(x), x, -oo)
Lopital's rule
There is no sense to apply Lopital's rule to this function since there is no indeterminateness of 0/0 or oo/oo type
The graph
0
2
4
6
8
-8
-6
-4
-2
-10
10
-20000
20000
Plot the graph
Rapid solution
[src]
0
0
0
0
Expand and simplify
Other limits x→0, -oo, +oo, 1
lim
x
→
−
∞
(
e
x
cos
(
x
)
)
=
0
\lim_{x \to -\infty}\left(e^{x} \cos{\left(x \right)}\right) = 0
x
→
−
∞
lim
(
e
x
cos
(
x
)
)
=
0
lim
x
→
∞
(
e
x
cos
(
x
)
)
=
⟨
−
∞
,
∞
⟩
\lim_{x \to \infty}\left(e^{x} \cos{\left(x \right)}\right) = \left\langle -\infty, \infty\right\rangle
x
→
∞
lim
(
e
x
cos
(
x
)
)
=
⟨
−
∞
,
∞
⟩
More at x→oo
lim
x
→
0
−
(
e
x
cos
(
x
)
)
=
1
\lim_{x \to 0^-}\left(e^{x} \cos{\left(x \right)}\right) = 1
x
→
0
−
lim
(
e
x
cos
(
x
)
)
=
1
More at x→0 from the left
lim
x
→
0
+
(
e
x
cos
(
x
)
)
=
1
\lim_{x \to 0^+}\left(e^{x} \cos{\left(x \right)}\right) = 1
x
→
0
+
lim
(
e
x
cos
(
x
)
)
=
1
More at x→0 from the right
lim
x
→
1
−
(
e
x
cos
(
x
)
)
=
e
cos
(
1
)
\lim_{x \to 1^-}\left(e^{x} \cos{\left(x \right)}\right) = e \cos{\left(1 \right)}
x
→
1
−
lim
(
e
x
cos
(
x
)
)
=
e
cos
(
1
)
More at x→1 from the left
lim
x
→
1
+
(
e
x
cos
(
x
)
)
=
e
cos
(
1
)
\lim_{x \to 1^+}\left(e^{x} \cos{\left(x \right)}\right) = e \cos{\left(1 \right)}
x
→
1
+
lim
(
e
x
cos
(
x
)
)
=
e
cos
(
1
)
More at x→1 from the right
The graph